Damage mechanisms evolution of ductile cast irons under thermomechanical loadings. (1st January 2013) - Hervas, Isabel; Ben Bettaieb, Mohamed; Hug, Eric
In this work, tensile and compression tests were carried out on ferritic cast iron samples in order to understand the influence of the stress state for temperatures until 800°C. Results show an asymmetric behaviour of ductile cast iron (DCI). The damage created during hardening was evaluated using local microstructural quantifications. Several damage differences are highlighted at room temperature. Therefore, when temperature increases, differences between damage mechanisms under tension and under compression are amplified. A relation between nodules deformation experimentally determined at different stress-strain stages and numerical simulation is proposed. The numerical predictions are in good agreement with the distribution of the aspect ratio (the ratio between major and minor axis of nodules) obtained experimentally. It was noted that nodules deformation can represent the total material strain at room temperature. In addition, it was shown that graphite nodules in cast iron cannot always be assimilated to voids during the strain.